Blackbox Testing of Primakara University's New Student Admissions Information System (PMB) Based on Equivalence Partitions and SUS Questionnaire - Subawa, I Made Ary (JATISI, 2025)
Primakara University has developed a New Student Admissions (PMB) information system that is used to facilitate prospective new students in registering anywhere. Therefore, it is necessary to test the New Student Admissions (PMB) information system of Primakara University to perfect the newly developed information system. Testing is carried out using the Blackbox method based on Equivalence Partitions aimed at finding out whether the information system being developed still has bugs or errors. Testing is also carried out using the SUS Questionnaire method to produce user perceptions regarding the New Student Admissions system being developed. The results of the blackbox test show that the system's functionality is running well, namely no errors were found. The results of the SUS Questionnaire test show that the New Student Admissions information system is in category D, namely OK.